The research on unmanned aerial vehicle remote sensing and its applications - Li Changchun; Shen Li; Wang Hai-bo; Lei Tianjie (2010 2nd International Conference on Advanced Computer Control, 2010)
As an important means of obtaining spatial data, the unmanned aerial vehicle (UAV) remote sensing has such advantages as real-time, flexible, high-resolution, cost-effective etc, and it can gather information in dangerous environments without risk to flight crews. Because UAV remote sensing is a powerful supplement of spaceborne remote sensing and airborne remote sensing, it has enormous potential and bright prospect. In this paper, the compositions and key technologies of UAV remote sensing system are presented, and the applications such as land use, land supervision, flood disasters, meteorology disasters, geological disasters, forest fire disasters as well as surveying and mapping are summarized. In the end, we predict the main direction of studying on UAV remote sensing in the future.